2002
DOI: 10.1023/a:1021343825552
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The expression of vitamin D-receptor (VDR) and retinoid X-receptor alpha (RXR-alpha) has been analysed immunohistochemically in benign (n = 62 and n = 5 respectively) and malignant (n = 228 and n = 15 respectively) breast tissue samples using a monoclonal antibody 9A7gamma against VDR and a polyclonal antibody against RXR-alpha. A recently developed immunoreactive scoring method (IRS) was employed. The expression of VDR was detected at the RNA-level using the reverse transcriptase-polymerase chain reaction. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…Some studies have demonstrated that the VDR protein is expressed in samples from normal breast tissues and also in breast cancer biopsy specimens [14,15,24,25]. Our results have shown that the VDR is expressed in carcinomas.…”
Section: Discussionsupporting
confidence: 73%
“…Some studies have demonstrated that the VDR protein is expressed in samples from normal breast tissues and also in breast cancer biopsy specimens [14,15,24,25]. Our results have shown that the VDR is expressed in carcinomas.…”
Section: Discussionsupporting
confidence: 73%
“…In contrast to numerous studies on circulating vitamin D biomarkers and breast cancer, there are few studies on VDR expression in breast tumor tissues. In an earlier study of 228 breast cancer patients, VDR expression was not associated with any histopathological indicators, such as ER and Ki-67 status (20). Moreover, previous studies have shown VDR expression as a prognostic marker for prostate and lung cancer (21, 22), which has remained understudied in breast cancer.…”
Section: Introductionmentioning
confidence: 95%
“…Reports suggest that down-regulation of RAR␣ during tumor progression coincides with loss of response to RAR ligand (33), and the loss of RAR␤ is commonly observed at the early stage of tumorigenesis in multiple cancers (3). Conversely, every RXR isotype is overexpressed in 66% of breast ductal carcinomas in in situ lesions (8), and in particular RXR␣ up-regulation is associated with malignant transformation (34). Collectively, these data indicate that activation of RXR/RXR homodimer may require exogenous RXR-ligand and high RXR expression, and the aberrant expression profile of RAR and RXR in tumors may provide an advantage for RXR-ligand-induced cancer therapy.…”
Section: P21mentioning
confidence: 99%